The Representation of Prabowo Subianto in the Jakarta Post’s 2024 Presidential Election Coverage - Silvia Damayanti Puspaningrum; Ingatan Gulö (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The representation of Prabowo Subianto in The Jakarta Post's coverage of the 2024 Indonesian presidential election is analyzed using Fairclough's Critical Discourse Analysis (CDA). This study used a descriptive qualitative method since it is more appropriate for analyzing data. The data were in the form of words, sentences and phrases. The data was collected from the Indonesian online news media called The Jakarta Post about Prabowo Subianto around the 2024 presidential election. The purpose of this study is to determine how language and discourse are used to represent Prabowo Subianto, as well as what these representations mean in the Indonesian political environment. The study investigates the text analysis, discourse practices analysis, and socio-cultural practices analysis represented in newspaper stories using a three-dimensional framework of description, interpretation, and explanation. The results show that Prabowo's actions and influence over politics are highlighted by The Jakarta Post through material processes, and high-value modality further supports an assertive, strong image. Based on the representation, it appears like Prabowo is being shown as a strong and competent candidate. In light of these findings, it is advised that readers engage critically with news sources in order to create balanced interpretations.